The association between coracoacromial ligament morphology and rotator cuff tears: A cadaveric study. Issue 4 (8th December 2021) - Alraddadi, Abdulrahman; Alashkham, Abduelmenem; Lamb, Clare; Soames, Roger
Abstract: To determine the association between coracoacromial ligament (CAL) morphology and rotator cuff tears. The present study is a prospective cohort study based on the dissection of 172 shoulders from 86 (46 female, 40 male) formalin embalmed European Caucasian cadavers, with a median age of 82 years. The anatomy of CAL was examined, including its morphology and parametric measurements, while the rotator cuff tendons were inspected for the presence of tears. Gross examination of the CAL in 155 shoulders revealed a variable number of bands as follows: 28 (18%) had one band, 56 (36%) two bands and 71 (46%) three or more bands. Inspection of the rotator cuff tendons showed the presence of tears in 77 (50%) shoulders, of which 37 (24%) were partial and 40 (26%) were full‐thickness tears. Statistical analysis showed a significant association ( P < 0.05) between CAL band number and the prevalence of a rotator cuff tear. A high proportion of rotator cuff tears were observed in shoulders with two (52%) and three or more CAL bands (56%) compared to single band ligaments (29%). Parametric assessment of the CAL in shoulders with rotator cuff tears showed significantly greater ( P < 0.05) attachment widths and ratios, thicker ligament bands, and larger cross‐sectional areas compared to the control group. Coracoacromial ligaments with more than a single band have a strong association with rotator cuff tears.